The Participation of Teachers in Greece in Outdoor Education Activities and the Schools' Perceptions of the Benefits to Students - Anastasia Chrysomalidou; Ioannis Takos; Ioannis Spiliotis; Panteleimon Xofis (MDPI AG, 2024)
International research highlights the potentially valuable contribution of outdoor education to the healthy development and proper holistic education of students. Among the various benefits that students gain from participating in outdoor activities are the mitigation of symptoms of Attention Deficit Hyperactivity Disorder (ADHD), improved respiration, memory improvement, skills development and others. Despite the well-documented contribution of such activities to children's wellbeing, there is an increasing trend of younger children lacking contact with nature. The current study investigates to what extent teachers in Greece, at schools where students aged 6-18 attend, provide opportunities for outdoor activities to their students. Furthermore, it investigates the teacher's perceptions of the benefits the students gain from such activities, based on their personal experience and the experience of other co-teachers in their school. The results presented in this study indicate that the percentage of teachers who choose outdoor activities during the educational process in Greece is rather low, although they identify that such activities provide significant benefits to students. Based on the perceptions of teachers regarding the mental, cognitive and physical benefits that students gain from outdoor activities a positive association was found between the participation of students in such activities and these benefits. Therefore, this study reveals that it is of significant importance to increase the number of opportunities for students' participation in outdoor learning activities, by supporting teachers, creating learning communities with them and empowering them to provide more outdoor learning opportunities.